Assessment of the Confidence of the Adhesive Remnant Index Score With Different Methods - A. Alper Öz; Sabahat Yazicioğlu; Nursel Arici; Berat Serdar Akdeniz; Naci Murat; Selim Arıcı (Galenos Yayinevi, 2013)
Objective:The purpose of this in vitro study was to investigate the reliability of the adhesive remnant index (ARI) score system with different assessment methods and to test the compatibility of the estimators.Materials and Methods:Sixty-eight human premolars were used in this study. The premolar brackets (SmartClip, 3M Unitek, Monrovia, CA, USA) were bonded with a light cure adhesive (Transbond XT, 3M Unitek). Brackets were debonded using a Lloyd LRX testing machine (Lloyd Instruments Plc., Fareham, Hampshire, UK). Special image analysis software with ×20 magnification and naked-eye assessment methods were used to evaluate the adhesive remnant. Four different investigators scored the same samples according to a 4-point scale. The Kendall rank correlation coefficient was used to test the reliability of the estimator's scores. The Friedman test, followed by the Wilcoxon signed-ranks test, was used to investigate significant differences in the ARI scores between the different assessment methodsResults:The Kendall rank correlation coefficients revealed no significant difference between the scores assigned by the investigators in this study. However, the ARI scores were significantly different when the special image analysis program was used (p < 0.05).Conclusion:The reliability of the ARI scores increased when quantitative measurement methods were used.